Environmental Controls Over Actinobacteria Communities in Ecological Sensitive Yanshan Mountains Zone - Tang, Hui; Shi, Xunxun; Wang, Xiaofei; Hao, Huanhuan; Zhang, Xiu-Min; Zhang, Li-Ping (Frontiers in Microbiology, 2016)
The Yanshan Mountains are one of the oldest mountain ranges in the world. They are located in an ecologically sensitive zone in northern China near the Hu Huanyong Line. In this metagenomic study, we investigated the diversity of Actinobacteria in soils at 10 sites (YS1–YS10) on the Yanshan Mountains. First, we assessed the effect of different soil prtreatment on Actinobacteria recovery. With the soil pretreatment method: air drying of the soil sample, followed by exposure to 120 oC for 1 h, we observed the higher Actinobacteria diversity in a relatively small number of clone libraries. No significant differences were observed in the Actinobacterial diversity of soils from sites YS2, YS3, YS4, YS6, YS8, YS9, or YS10 (P > 0.1). However, there were differences (P < 0.05) from the YS7 site and other sites, especially in response to environmental change. And we observed highly significant differences (P < 0.001) in Actinobacterial diversity of the soil from YS7 and that from YS4 and YS8 sites.. The climatic characteristics of mean active accumulated temperature, annual mean precipitation, and annual mean temperature, and biogeochemical data of total phosphorus contributed to the diversity of Actinobacterial communities in soils at YS1, YS3, YS4, and YS5 sites. Compared to the climatic factors, the biogeochemical factors mostly contributed in shaping the Actinobacterial community. This work provides evidence that the diversity of Actinobacterial communities in soils from the Yashan Mountains show regional biogeographic patterns and that community membership change along the north-south distribution of the Hu Huanyong Line.